Plan de capacitación para el turismo sostenible y desarrollo local de la comunidad Chiguilpe, cantón Santo Domingo de los Tsachila año 2022 - Muñoz Carriel, Irving Alexander (2022)
This research work is a compilation of information on the history, culture, way of life, customs, traditions, crafts, gastronomy that can be enjoyed and known through sustainable tourism and local development of the Chigüilpe community, of the Santo Domingo of Tsáchilas, for this reason it was taken bibliographical sources that help support all the information acquired, the same that serve the development of the present investigative work. One of the main problems found during the situational analysis carried out through the investigation was that the lack of government support, added to a lack of interest in cultural preservation among Ecuadorian citizens and foreigners who They also do not have adequate communication channels to find out about the offer, they have caused that the tourist ventures of the Chigüilpe community, do not have enough reception. Starting from there, a series of alternatives based on strategic communication are proposed, to ensure that the tourist influx to Chigüilpe is greater, based on cultural strengthening and respect.